2003
DOI: 10.1001/archderm.139.3.325
|View full text |Cite
|
Sign up to set email alerts
|

Narrowband UV-B (TL-01) Phototherapy vs Oral 8-Methoxypsoralen Psoralen–UV-A for the Treatment of Chronic Plaque Psoriasis

Abstract: Objective: To compare the efficacy of narrowband UV-B (TL-01) phototherapy with oral 8-methoxypsoralen photochemotherapy (8-MOP psoralen-UV-A [PUVA]) in patients with chronic plaque psoriasis (CPP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
80
6
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 26 publications
(32 reference statements)
10
80
6
4
Order By: Relevance
“…13 In the present study, there was no statistically significant difference in the number of patients who achieved reduction in MPASI ≥75% with both modalities (85.18% on PUVA side and 81.48% on NB-UVB side; p value 0.718). This is in agreement with the previous studies done by Tanew et al 2 who also found statistically similar clearance rates of 43% for PUVA and 33% for NB-UVB, and Markham et al 15 who found very high clearance rates of 100% for both PUVA and NB-UVB. Such high clearance rates can be explained on the basis that the patients in Markham's study were treated until they were completely clear.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…13 In the present study, there was no statistically significant difference in the number of patients who achieved reduction in MPASI ≥75% with both modalities (85.18% on PUVA side and 81.48% on NB-UVB side; p value 0.718). This is in agreement with the previous studies done by Tanew et al 2 who also found statistically similar clearance rates of 43% for PUVA and 33% for NB-UVB, and Markham et al 15 who found very high clearance rates of 100% for both PUVA and NB-UVB. Such high clearance rates can be explained on the basis that the patients in Markham's study were treated until they were completely clear.…”
Section: Discussionsupporting
confidence: 93%
“…13 Regimens similar to ours were used by Tanew et al 2 and Tahir et al 14 while van Weelden et al, 12 Gordon et al 6 and Yones et al 8 used the twice weekly regimens. A very different twice weekly frequency for PUVA and thrice weekly frequency for NB-UVB was used by Dawe et al 4 and Markham et al 15 in their studies. However, the kind of regimens used did not have any effect on the outcome of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the numerous trials performed on the efficacy ofPUVA and UVB-NB (16)(17)(18), scarce data are available on the different duration of remission induced by these two phototherapeutic regimens. Our data show that, although the difference of the duration of remission is not statistically significant, a trend is seen and patients treated with PUVA remain clear for a period about 88 days longer than that.of patients treated with UVB-NB.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of efficacy instead, 311 nm UVB phototherapy is comparable to PUVA therapy, with a better tolerability profile (11).…”
Section: Discussionmentioning
confidence: 99%
“…This process mainly targets T-lymphocytes in the epidermis of skin lesions in atopic and psoriasis patients (10)(11)(12).…”
mentioning
confidence: 99%